Elexacaftor/Tezacaftor/Ivacaftor Efficacy in a Cohort of Italian Patients with CFTR Rare Mutations - Francesca Lucca; Sonia Volpi; Mirco Ros; Benedetta Fabrizzi; Ilaria Meneghelli; Marica Bordicchia; Francesca Buniotto; Alessia Lancini; Cecilia Brignole; Francesca Pauro; Valentino Bezzerri; Marco Cipolli (International Journal of Translational Medicine)
Background: Cystic Fibrosis is an inherited disorder caused by mutations in the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) gene, encoding a chloride and bicarbonate channel widely expressed in epithelia. Loss of CFTR function leads to dehydration of the epithelium surface with thicker mucus secretions from tissues. The lungs, pancreas, liver, intestines, and sweat glands are the most common affected organs. However, pulmonary disease remains the main cause of morbidity and mortality. Fortunately, elexacaftor/tezacaftor/ivacaftor (ETI) therapy is showing unprecedented clinical benefits in patients with Cystic Fibrosis (CF) carrying at least one F508del mutation in the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) gene. However, almost 35% of the CF population living in the Mediterranean area still lacks effective CFTR modulator therapies because of the elevated incidence of patients with (pw)CF harboring CFTR rare mutations (RMs), different from F508del. Methods: Twenty-three pwCF harboring RM including the N1303K underwent off-label ETI treatment for 6-12 months. Respiratory function in terms of FEV1 and FVC was measured after 3, 6, and 12 months of treatment. In addition, we analyzed sweat chloride concentration, body mass index (BMI), and quality of life before and after treatment. Possible adverse effects were recorded. Results: All patients included in this off-label program displayed a substantial improvement in respiratory function. In particular, patients carrying the N1303K mutation showed an improvement in FEV1 and FVC similar to that observed in subjects harboring the F508del mutation, although sweat chloride concentration was not significantly decreased. No severe adverse effect was reported. Conclusions: This study strengthens the clinical efficacy of ETI in pwCF harboring the N1303K and other CFTR rare variants. Since these CFTR RMs have not been approved for ETI therapy in Europe, this study may promote the inclusion of these variants in the list of CFTR mutations responsive to ETI.